2008
DOI: 10.1021/jf072782m
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Contents of Oleoresin and Pungent Bioactive Principles of Jamaican Ginger (Zingiber officinale Roscoe.) during Maturation

Abstract: Changes in the yields of the oleoresin and content of pungent bioactive principles: [6], [8], [10] gingerols and [6] shogaol of Jamaican ginger ( Zingiber officinale) were investigated during different stages of maturity (7-9 months). Ethanolic oleoresin extracts were prepared (95%, w/w) by cold maceration of dried ginger powder, and their percentage yields were calculated (w/w). The pungent bioactive principles in the ginger oleoresin were extracted with methanol and quantitatively analyzed by high performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 6 publications
0
32
0
Order By: Relevance
“…However, the oleoresin yield of 9-month-matured NER ginger cultivars in this study was found to be higher than Cochin ginger (4.25%) and closer to ginger from Sierra Leone (7.2%), Nigerian ginger (6.5%), and Ghana ginger (5.7%). 3 Two Jamaican ginger cultivars showed 7.25% (Bourbon and Portland) and 7.18% (Retreat and St. Mary) of the oleoresin yield at 9-month maturity, 16 which are found to be similar to the Tripura II cultivar.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…However, the oleoresin yield of 9-month-matured NER ginger cultivars in this study was found to be higher than Cochin ginger (4.25%) and closer to ginger from Sierra Leone (7.2%), Nigerian ginger (6.5%), and Ghana ginger (5.7%). 3 Two Jamaican ginger cultivars showed 7.25% (Bourbon and Portland) and 7.18% (Retreat and St. Mary) of the oleoresin yield at 9-month maturity, 16 which are found to be similar to the Tripura II cultivar.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…Many qualitative and/or quantitative methods have been reported for analysis of fresh (1618,23) and dried ginger (24). A variety of solvents such as methanol (16, 17), ethanol (18,25), DCM (23), acetone (25), and pressurized CO 2 (19,20) have been used for ginger extraction.…”
Section: Resultsmentioning
confidence: 99%
“…[10] A large number of HPLC and HPTLC methods for the quantification of 6-gingerol in [11,12] ginger oil, [13] crude drugs drink, [14] commercial Ayurvedic formulation [15] and rhizome [16] have been reported in the literature. The literature survey also revealed that quantification of other ginger homologues (8,10 gingerols) with 6-gingerol, [17] other diterpenes in Japanese gingers, [18] green and dried ginger, [19] freeze dried CO 2 extract, [20] three gingerols [21] with 6-shogaol in Jamaican ginger, [22] commercial ginger, fresh and dried rhizome and dietary supplements, [23][24][25] with have also been reported. Until date, no report on chromolithic separation of 6, 8, 10-gingerols and shogaol for the quantification, validation and system suitability in the ginger rhizome has been reported.…”
Section: Hplc Apparatus and Chromatographic Conditionsmentioning
confidence: 99%